Experimental systems to assess the effects of reactive oxygen species in plant tissues - Maurino, Verónica G (Landes Bioscience, 2008)
Reactive oxygen species (ROS) are continuously produced in several organelles during aerobic metabolism. Furthermore, a wide range of environmental stresses such as chilling, salinity, drought and high light, lead to an elevated production of ROS. ROS can react with biomolecules and cause oxidative damage and even necrosis. Antioxidants and antioxidant-enzymes function to interrupt the cascades of uncontrolled oxidation. On the other hand, ROS influence the expression of genes playing a central role in many signaling pathways. Tools like the exogenous application of oxidative stress-causing agents and the in planta production of ROS in mutants altered in ROS metabolism are increasingly used to assess specific and common responses toward different types of ROS signals. The major challenge is the identification of ROS sensors and signaling components to finally elucidate the molecular mechanisms of oxidative stress response in plants.